Investigation of the influence of the parameters of the experimental spiral potato heap separator on the quality of work - Bulgakov, V.; Ivanovs, S.; Adamchuk, V.; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич (My University, 2017)
The known designs of potato heap cleaners have a series of disadvantages, particularly on sticky soils. In the newly developed and patented potato heap cleaner of a spiral type there is used the vibration effect and other technical solutions which ensure efficient self-cleaning of the rollers. Laboratory-field equipment was worked out and made for the investigations which had a spiral potato heap cleaner of a new design mounted on it. Under the field conditions the real technological process of digging and cleaning of the potato tubers from the soil admixtures was simulated in one row of the potato plantation. By using the developed methodology of a multifactor experiment dependencies were obtained characterising the impact of the design and kinematic parameters of the cleaner itself upon the quality indicators of its operation (the soil separation efficiency, the cleanness of the heap, the damage and losses of the tubers), allowing optimisation of the design.
Keywords: potatoes; harvesting; separator; spiral tool; multi-factor experiment